Targeting Necroptosis: A Novel Therapeutic Option for Retinal Degenerative Diseases - Qí Zhāng; Xi‐min Hu; Wenjuan Zhao; Xiao-xia Ban; Yan Li; Yanxia Huang; Hao Wan; Ye He; Lvshuang Liao; Lei Shang; Bin Jiang; Guoping Qing; et al. (2023)
The discovery of the necroptosis, a form of regulated necrosis that is mediated by receptor-interacting protein kinase 1 (RIPK1), RIPK3, and mixed-lineage kinase domain-like pseudokinase (MLKL), represents a major breakthrough that has dramatically altered the conception of necrosis -traditionally thought of as uncontrolled cell death -in various human diseases.Retinal cell death is a leading cause of blindness and has been identified in most retinal diseases, e.g., age-related macular degeneration, glaucoma, retinal detachment, retinitis pigmentosa, etc. Increasing evidence demonstrates that retinal degenerative diseases also share a common mechanism in necroptosis.Exacerbated necroptotic cell death hinders the treatment for retinal degenerative diseases.In this review, we highlight recent advances in identifying retinal necroptosis, summarize the underlying mechanisms of necroptosis in retinal degenerative diseases, and discuss potential anti-necroptosis strategies, such as selective inhibitors and chemical agents, for treating retinal degenerative diseases.